ĐÁNH GIÁ ĐỘC TÍNH CẤP VÀ ĐỘC TÍNH BÁN TRƯỜNG DIỄN CỦA CHẾ PHẨM THUỐC TIÊM FENTANYL NGHIÊN CỨU BÀO CHẾ TRONG NƯỚC - Vũ, Mạnh Hùng; Lê, Thị Hồng Hạnh; Phạm, Duy Nam (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
THE EVALUATION OF ACUTE AND SUBCHRONIC TOXICITY OF DOMESTICALY STUDIED AND MANUFACTURED FENTANYL INJECTIONFentanyl injection is very important drug and widely used for anesthesia and analgesia during and post surgery. This paper presents the results of acute and subchronic toxicity studies of the domesticaly studied and manufactured fentanyl injection. The lethal dose of the fentanyl found in intravenous injection in mice is LD50=6.17±0.38 mg/kg and in subcutaneous injection is LD50=58.33 ± 11.22 mg/kg.The study of subacute and subchronic toxicity showes, that the fentanyl at the daily dose 100μg/kg ÷ 300 μg/ kg given to subcutaneous injection to mice in 6 consecutive weeks had no influence on the general state and the biochemical hematopoietic, hepatic and renal function of mice. In the histopathological study, FC caused no injuries in the liver, spleen and kidneys.